2017
DOI: 10.1016/j.matdes.2016.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and tribological properties of Cr3C2/Ni3Al composite materials prepared by hot isostatic pressing (HIP)

Abstract: Fe) phase is formed in Cr 3 C 2 /Ni 3 Al composites prepared by hot isostatic pressing. • The hardness of the Cr 3 C 2 /Ni 3 Al composites increases with increasing addition of Cr 3 C 2. • The wear resistance of Cr 3 C 2 /Ni 3 Al composites is improved due to the Cr 3 C 2 asperities keep the sliding surfaces apart. • Excess addition of Cr 3 C 2 (such as 24 vol%) can decrease the wear resistance of Cr 3 C 2 /Ni 3 Al composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 29 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…Cu/Ti3SiC2/C/Graphene nanocomposite materials were designed based on the concept of multi-phase composites and prepared by powder metallurgy re-pressing methods-that is, VHP sintering and HIP. The process includes mechanical ball-milling, compacting, and sintering process in which a component is subjected to both elevated temperature and high pressure [44].The physical parameters of graphene, graphite powder, Ti3SiC2 powder, and electrolytic copper powder used as raw material are listed in Table 1. Dispersions of graphene assisted by ultrasonic oscillation, plasma, and chemical treatment surface modification were prepared using Ar-NH3 plasma and 0.02µg/mL rutin solution [45][46].The raw powders consisting of 10 wt.% Ti3SiC2, 3 wt.% graphite, different contents of graphene (0.5 wt.%, 1.0 wt.%, 1.5 wt.%) and copper were mixed by high-energy ball milling for 1 h. Composite powders were heated from room temperature to 950°C and applied with pressure of 27.7 MPa for 30min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu/Ti3SiC2/C/Graphene nanocomposite materials were designed based on the concept of multi-phase composites and prepared by powder metallurgy re-pressing methods-that is, VHP sintering and HIP. The process includes mechanical ball-milling, compacting, and sintering process in which a component is subjected to both elevated temperature and high pressure [44].The physical parameters of graphene, graphite powder, Ti3SiC2 powder, and electrolytic copper powder used as raw material are listed in Table 1. Dispersions of graphene assisted by ultrasonic oscillation, plasma, and chemical treatment surface modification were prepared using Ar-NH3 plasma and 0.02µg/mL rutin solution [45][46].The raw powders consisting of 10 wt.% Ti3SiC2, 3 wt.% graphite, different contents of graphene (0.5 wt.%, 1.0 wt.%, 1.5 wt.%) and copper were mixed by high-energy ball milling for 1 h. Composite powders were heated from room temperature to 950°C and applied with pressure of 27.7 MPa for 30min.…”
Section: Methodsmentioning
confidence: 99%
“…sintering process of the copper matrix (i.e., formation of a sintering neck), increases the number of voids, and increases porosity. be compressed to an oblate form after single-phase loading during VHP sintering [44]. The diameter of the copper particles in direction I is smaller than that in direction II.…”
Section: Microstructure and Phase Identification Of Nanocomposite Materialsmentioning
confidence: 99%
“…Their manufacturing typically involves casting, [5] cold rolling, [6] and powder metallurgy technologies. [7,8] Recently, additive manufacturing has attracted significant attention because of its digital, flexible, and controllable fabrication process for the direct and fast production of metal components. [9] Application of additive manufacturing on Ni-based superalloy, e.g., precipitation hardening type Inconel 738 alloy, provides a new perspective for prototype manufacturing of Ni 3 Al superalloy components.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have shown that the high temperature strength and hardness of Ni 3 Al alloy can be significantly increased by adding Cr 3 C 2 particles, which have the advantages of high hardness, high-temperature stability, excellent high-temperature wear resistance, high compatibility, and wettability with the Ni 3 Al matrix [9][10][11][12]. Fu et al [13] prepared a Cr 3 C 2 /Ni 3 Al composite material using hot isostatic pressing technology, and studied the influence of different chromium carbide contents on the wear resistance of the composite. It was found that a certain content of chromium carbide can effectively improve the wear resistance of the material.…”
Section: Introductionmentioning
confidence: 99%